Modulation: A Translation Method to Obtain Naturalness in Target Language Texts - Adventina Putranti (Universitas Sanata Dharma, 2018)
One of the requirements in order to produce equivalent translation is that the translation must sound natural for target language (TL) readers both lexically and grammatically. This naturalness can be obtained through the use of both lexical items and grammar familiar to the TL readers. However, naturalness in translation is not always easy to achieve. One of the causes is the difference in the way the source language (SL) and TL readers express a certain message in their languages. According to Vinay and Darbelnet (1995) this difference can be overcome by applying a translation method called modulation. Modulation is a method in which translators try to maintain naturalness by using various form the message done by changing the point of view. This procedure is usually chosen when translators find that literal translation would result in awkward or unnatural translation.Keywords: modulation, naturalness, equivalence